STUDI MODERASI BERAGAMA DALAM KURIKULUM PESANTREN MA MATHALI’UL FALAH DAN SMK SALAFIYAH KAJEN MARGOYOSO PATI - Isytaharo Amroh; Sutriasih .; Samsul Munir; Lutfan Muntaqo (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2022)
The cultivation of religious moderation needs to be taken seriously in all walks of life. So that radicalism, intolerance, and terrorism can be prevented from an early age. Ministry institutions, companies, schools, madrasahs, and islamic boarding schools are no exception. Moderate Islam has always prioritized tolerance, not violence, mutual respect, not self-defeating while still believing in the truth of the beliefs of each religion and madzhab. The curricula that is developing today seems monotonous but quickly changing validity in the world of education cannot cover the turmoil of the phenomena that are circulating. From this paper, the researcher tries to provide information about the implementation of the main curriculum in the pesantren-based school area, that thepesantren k uriculum can have its own freedom and flexibility to design, compile, shape determine and implement its systems and curriculum to be able to underlie students in religious moderation.